KADAR SUBSTANSI P SERUM TINGGI SEBAGAI FAKTOR RISIKO CHRONIC TENSION TYPE HEADACHE PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Daniel Siagian; Made Oka Adnyana; Putu Eka Widyadharma (PERDOSNI, 2020)
HIGH SUBSTANCE P SERUM LEVELS AS RISK FACTOR FOR CHRONIC TENSION TYPE HEADACHE AMONG MEDICAL STUDENT FACULTY OF MEDICINE UDAYANA UNIVERSITYABSTRACTIntroduction: Several studies revealed that serum substance P (SP) levels increase in people with headache, particularly chronic tension-type headache (CTTH). One of the examples of population at risk of CTTH is medical students because of their stressful academic load. Aim: To determine whether high serumSP levels are the risk factors of CTTH among medical students.Methods: A case-control study was conducted to medical students, aged 19 to 21, of the Faculty of Medicine, Udayana University from December 2018 to January 2019. Subjects were classified into case group (with CTTH) and control group (without CTTH). SP serum levels were measured on both groups. Analyses included univariate, bivariate with Fisher's test to calculate relative risk (RR), and multivariate logistic regression analysis.Results: Sixty-two subjects, predominantly female (51.6%), were involved in this study. In the case group, most of the subjects had mild depression (71%), mild stress (93.5%), pericranial tenderness (61,3%), and elevated SP serum levels (83.9%). From the multivariate analysis, a high level of SP serum (≥ 349,06ng/L) was the risk factor of CTTH (adjusted Odds ratio 9.9; 95% CI 1.06-93.16). Besides that, other factors, for example, mild stress, mild anxiety, mild depression, pericranial tenderness, and sleep disturbances, were related to the prevalence of CTTH(p=0.001).Discussion: This study concluded that high serum SP levels significantly increased the risk of CTTH occurrence among medical students.Keywords: Chronic tension-type headache (CTTH), medical student, SP serum levelsABSTRAKPendahuluan: Beberapa penelitian menunjukkan kadar substasi P (SP) serum meningkat pada penderita chronic tension type headache (CTTH). Salah satu populasi yang rentan mengalami CTTH adalah mahasiswa kedokteran karena beban akademik relatif tinggi yang diduga berkaitan dengan stres psikologis.Tujuan: Mengetahui apakah kadar SP serum merupakan salah satu faktor risiko CTTH pada mahasiwa kedokteran.Metode: Studi kasus kontrol dilakukan terhadap mahasiswa Fakultas Kedokteran Universitas Udayana berusia 19-21 tahun pada bulan Desember 2018 hingga Januari 2019. Subjek dikelompokkan ke dalam kelompok kasus (dengan CTTH) dan kontrol (tanpa CTTH), kemudian seluruhnya diperiksakan kadar SP serum. Analisis data dilakukan secara univariat, bivariat dengan uji Fisher untuk menghitung risiko relatif (RR), dan analisis regresi logistik multivariat.Hasil: Sebanyak 62 subjek yang mayoritas perempuan (51,6%) ikut serta dalam studi ini. Pada Pada kelompok kasus, sebagian besar mengalami depresi ringan (71%), stres ringan (93,5%), nyeri tekan perikranial (61,3%), dan memiliki kadar SP serum yang tinggi (83,9%). Berdasarkan analisis multivariat, kadar SP serum tinggi (≥ 349,06ng/L) merupakan faktor risiko CTTH (adjusted rasio Odds 9,9; IK 95% 1,06-93,16). Selain itu, faktor depresi ringan, stres ringan, ansietas ringan, nyeri tekan perikranial, dan gangguan tidur masing-masing berhubungan dengan kejadian CTTH (p=0,001).Diskusi: Kadar SP serum tinggi merupakan faktor risiko terjadinya CTTH pada populasi mahasiswa kedokteran.Kata kunci: Chronic tension type headache (CTTH), mahasiswa kedokteran, substansi P